2020
DOI: 10.3389/fpsyg.2020.575497
|View full text |Cite
|
Sign up to set email alerts
|

Shrinking Your Deictic System: How Far Can You Go?

Abstract: Languages around the world differ in terms of the number of adnominal and pronominal demonstratives they require, as well as the factors that impact on their felicitous use. Given this cross-linguistic variation in deictic demonstrative terms, and the features that determine their felicitous use, an open question is how this is accommodated within bilingual cognition and language. In particular, we were interested in the extent to which bilingual language exposure and practice might alter the way in which a bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 46 publications
1
8
1
Order By: Relevance
“…This simplification of deictic reference is also consistent with the higher prevalence of two-term systems documented in the cross-linguistic survey in Diessel (2005Diessel ( , 2013. Importantly, the current binomial models replicate the results of Vulchanova et al (2020) with distance from speaker as the only significant predictor of deictic form used. This suggests that marking peri-personal space is a core feature of deictic systems across languages which is preserved also under deictic system shift (see also Diessel & Coventry, 2020).…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…This simplification of deictic reference is also consistent with the higher prevalence of two-term systems documented in the cross-linguistic survey in Diessel (2005Diessel ( , 2013. Importantly, the current binomial models replicate the results of Vulchanova et al (2020) with distance from speaker as the only significant predictor of deictic form used. This suggests that marking peri-personal space is a core feature of deictic systems across languages which is preserved also under deictic system shift (see also Diessel & Coventry, 2020).…”
Section: Discussionsupporting
confidence: 65%
“…Thus, overall, the Spanish Living in Norway used ese more than those living in Spain (58.3% vs. 38.3%), with minimal reduction in este (27.8% vs. 32.1%) and a notable drop in the use of aquel/aquella (13.9% vs. 29.1%). Multilevel regression models analyses revealed significant fixed effects for distance and for the Language × Distance interaction, but were not significant for language and for position of the hearer (see also Vulchanova et al, 2020). The descriptive data showed that aquel was used only 13.9% of the time in the SLiN group and there were empty cells for that item in the proximal region in the condition when the hearer was opposite.…”
Section: Analyses and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, the general understanding is that the encoding of indexicality in various contact settings is remarkably stable (see, a.o., Heine and Kuteva 2005;Friedman 2006;Matras 2009;Polinsky 2018), supporting the latter view. Against this background, recent investigations seem to suggest a more nuanced picture, with demonstrative forms possibly undergoing attrition in adult bilinguals (Vulchanova et al (2020); but the role of contact in these patterns of attrition has been downsized in Vulchanova et al (2022)). The cross-linguistic variation attested by demonstrative systems constitutes a fruitful window to further explore this issue, with the aim of understanding the role of contact in shaping syntactic variation and change in yet another domain of grammar.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In this section, I discuss some other (actual or conceivable) accounts for the reduction patterns and show that they fair overall less well; more specifically, I focus on: markedness-based accounts (C. Instead, I leave out of this discussion accounts that reduce (some instances of) change in demonstrative systems to the effects of contact (see, most recently, Vulchanova et al 2020;but cf. Vulchanova et al 2022 for partly different conclusions).…”
Section: C3 Alternative Accounts For Changementioning
confidence: 99%